Efektivitas Expressive Writing dalam Menurunkan Emosi Marah dan Stress Akademik Pada Siswa SMA di Kota Makassar - Irmayanti, Sri; Daud, Muh.; Ahmad, Ahmad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The problem in this research is the high level of academic stress accompanied by unstable management of angry emotions. This research aims to find out whether the expressive writing method can reduce angry emotions and academic stress for high school students in Makassar City. The experimental design used was The One Group Pretest-Posttest Design. The independent variable for this research is the expressive writing method and the dependent variables are the level of emotional anger and academic stress. Population on this research consisted of 622 students and the research sample was 22 students. Sample selection used non random sampling. Data were collected using the anger emotion scale and academic stress scale instruments. Data analysis uses descriptive statistical analysis and parametric analysis, namely the t test (Paired Sample T-Test). The research results showed that 1) there were differences in pretest/posttest scores for levels of academic stress and angry emotions which were divided into high, medium and low categories. 2) The implementation of expressive writing is carried out in accordance with the procedures designed through 4 sessions, namely recognition/initial write, examination/write exercise, Juxtapotitin/feedback, and application to the self. 3) There is a difference between the pretest and posttest scores on students' academic stress with a sig value (2-tailed) p= 0.016 (p<0.05) which means hypothesis 1 is accepted. 4) There was no difference between pretest and posttest scores on the management of students' angry emotions with a sig (2-tailed) value p = 0.0791 (p>0.05) which means hypothesis 2 was rejected.